A 24-year-old man with fibrodysplasia ossificans progressiva: clinical challenges and management - Abdal, Syed Jamil; Yesmin, Sabrina; Shahin, M. Abu; Islam, M. Ariful; Haq, Syed Atiqul; Nahar, Sharmin (International Journal of Research in Medical Sciences, 2025)
Fibrodysplasia ossificans progressiva (FOP) is a rare, disabling genetic disorder characterized by progressive heterotopic ossification of skeletal muscles and connective tissues. It is recognized as the most disabling condition of extraskeletal bone formation. The worldwide prevalence is approximately 1 in 2,000,000, with no ethnic, racial, gender, or geographic predilection. The hallmark clinical features include congenital malformation of great toes (commonly bilateral hallux valgus) and recurrent episodes of heterotopic ossification, often triggered by trauma or occurring spontaneously. Pathogenesis involves dysregulated bone morphogenetic protein (BMP) signaling due to mutation in the ACVR1 gene. Here we report a case of 24-year-old male with classical FOP, presenting with bilateral deformities of the big toes and progressive ectopic ossification. Despite advances in understanding the molecular mechanisms of the disease, there are currently no definitive preventive treatments. Early recognition of FOP, particularly by pediatric clinicians, is critical to avoid exacerbating factors, such as invasive procedures or trauma that may accelerate disease progression. This case report highlights the importance of clinical vigilance and continued research into therapeutic options for this devastating condition.